2018
DOI: 10.1002/mus.26061
|View full text |Cite
|
Sign up to set email alerts
|

Time‐course study of macrophage infiltration and inflammation in cast immobilization–induced atrophied muscle of mice

Abstract: Atrophy signaling pathway activation, but not macrophage infiltration, was observed during the early phase after cast immobilization. Our findings indicate that macrophage infiltration may contribute very little to the early phase of muscle atrophy after cast immobilization. Muscle Nerve 57: 1006-1013, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…This point was in agreement with some previous literature (28,29). Lengthy immobilization due to severe trauma, unwillingness, or pain caused muscle atrophy and capsular contracture (30).…”
Section: Discussionsupporting
confidence: 93%
“…This point was in agreement with some previous literature (28,29). Lengthy immobilization due to severe trauma, unwillingness, or pain caused muscle atrophy and capsular contracture (30).…”
Section: Discussionsupporting
confidence: 93%
“…Unexpectedly, we found that gene expression levels of atrophy-related genes were increased not only in Sol but also in EDL, and expression levels were higher in EDL than in Sol. MuRF1 and Atrogin-1 mRNA levels increased after 1 day of denervated, spinal cord-resected or cast-immobilized muscle, reached a peak at 3 days, and then decreased toward basal levels at 14 days (Sacheck et al 2007;Kawanishi et al 2018). Significant loss of muscle weight persisted until 14 days of disuse (Kawanishi et al 2018) and maximally decreased at 14-28 days (Sacheck et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…MuRF1 and Atrogin-1 mRNA levels increased after 1 day of denervated, spinal cord-resected or cast-immobilized muscle, reached a peak at 3 days, and then decreased toward basal levels at 14 days (Sacheck et al 2007;Kawanishi et al 2018). Significant loss of muscle weight persisted until 14 days of disuse (Kawanishi et al 2018) and maximally decreased at 14-28 days (Sacheck et al 2007). These findings indicated that, when actual muscle weight reduction occurred, there was no further upregulation of these genes.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism for the increase in FOXO3A expression is currently unclear. However, under catabolic states such as immobilization, FOXO3A expression is known to increase in skeletal muscle (Okamoto and Machida, ; Kawanishi et al, ). Considering these facts, FOXO3A is possibly involved in the bluntation of the muscle‐hypertrophic effect observed in the group with excessive shortening of the recovery period; thus, the involvement of FOXO proteins in the acceleration of protein ubiquitination, ubiquitin ligase mRNA expression, and autophagosome formation should be clarified in future investigations.…”
Section: Discussionmentioning
confidence: 99%